Impact of flavonoid-rich black tea and beetroot juice on postprandial peripheral vascular resistance and glucose homeostasis in obese, insulin-resistant men: a randomized controlled trial. Issue 1 (December 2016) - Fuchs, Dagmar; Nyakayiru, Jean; Draijer, Richard; Mulder, Theo; Hopman, Maria; Eijsvogels, Thijs; Thijssen, Dick
Abstract Background Insulin-stimulated muscle blood flow facilitates plasma glucose disposal after a meal, a mechanism that is impaired in obese, insulin-resistant volunteers. Nitrate- or flavonoid-rich products, through their proposed effects on nitric oxide, may improve postprandial blood flow and, subsequently, glucose disposal. To investigate whether a single dose of nitrate-rich beetroot juice or flavonoid-rich black tea lowers postprandial muscle vascular resistance in obese volunteers and alters postprandial glucose or insulin concentrations. Method In a randomised, controlled, cross-over study, 16 obese, insulin-resistant males consumed 75 g glucose, which was combined with 100 ml black tea, beetroot juice or control (water). Peripheral vascular resistance (VR), calculated as mean arterial pressure divided by blood flow, was assessed in the arm and leg conduit arteries, resistance arteries and muscle microcirculation across 3 h (every 30-min) after the oral glucose load. Results During control, we found no postprandial response in VR in conduit, resistance and microvessels (allP  > 0.05). Black tea decreased VR compared to control in conduit, resistance and microvessels (allP  < 0.05). Beetroot juice decreased postprandial VR in resistance vessels, but not in conduit artery and microvessels. Although postprandial glucose response was similar after all interventions, postprandial insulin response was attenuated by ~29 % after tea (P  < 0.0005), but not beetroot juice. Conclusions A single dose of black tea decreased peripheral VR across upper and lower limbs after a glucose load which was accompanied by a lower insulin response. Future studies in insulin-resistant subjects are warranted to confirm the observed effects and to explore whether long-term regular tea consumption affects glucose homeostasis. Trial registration The study was registered at clinicaltrials.gov on 30th November 2012 (NCT01746329 ).